Persepsi Masyarakat Hindu Terhadap Keberadaan Pasraman Formal Di Bali - Ni Komang Sutriyanti (Jurnal Kajian Bali (Journal of Bali Studies), 2020)
This paper aims to analyze the perception of Hindu society on the existence of formal pasraman (Hindu style of education) in Bali. The research method used is namely the type of qualitative research. This research of descriptive data with primary and secondary data sources and the technique of determining informants using purposive sampling techniques. Methods of data collection using observation techniques, interviews, literature studies, and documentation, as well as using data analysis techniques and presentation techniques of data analysis results. The results showed that first, the background of the establishment of a formal pasraman include juridical background, religious, and needs. Second, the learning method uses is catur pramana learning method. Third, the perception of Hindu society on the existence of formal pasraman is still low due to a lack of understanding as a whole, therefore it is necessary to socialize the existence of formal pasraman.Keywords: perception, learning methods, catur pramana, formal Hindu pasraman